THE ROLE OF RADIOLOGY NURSES IN MODERN HEALTHCARE - Mariam Swilam Daghash Alqahtani; Malak Hussain Mohammed Alahmari; Ahmed Talal Matar Almarshadi; Mesfer Saeed Shahwan Alwadei; Nourh Mohammed Alqadi; Saud Abdulaziz Saud Nafea; Eman Abdullah Abdulkareem Alturki; Budur Mohammed Naytol Alanazi; Saud Abdulaziz Saud Nafea; Nourah Mushabab Alahmari; Hassan Ali Jaghdami; Ahmed Turayhib Algethami; et al. (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
In the current healthcare system, radiology nurses play a crucial role in bridging the gap between patient-centered treatment and technology improvements. With an emphasis on patient advocacy, radiation safety, technological proficiency, and privacy, this study examines the ethical issues that arise in the practice of radiology nursing. Radiology nurses protect patient information by adhering to stringent privacy and confidentiality rules, and they also help healthcare providers communicate effectively. Radiology nurses put the safety of their patients first while dealing with ionizing radiation exposure, which includes advocating for dose optimization and following safety procedures. In order to manage the quickly changing technologies with professionalism, technological competence and integrity are critical qualities that call for ongoing education and ethical thought. The core of radiology nursing practice is patient advocacy, which supports patient empowerment, comfort, safety, continuity of care, and informed consent throughout the imaging process. In providing patient care, radiology nurses uphold the highest standards of professionalism, ethics, and compassion by adhering to these ethical imperatives.Aim: To detect the role of nurses in radiology and the prevention measures.